Wildcat - Morris, Amelia (Flatiron Books, 2022)
"Amelia Morris's Wildcat is an uproariously funny, surprisingly touching story of one woman's journey through motherhood and female friendship, in a society that plays fast and loose with information. New mother, aspiring writer, and former shopgirl Leanne has lost her way. As she struggles with both her grief and the haze of motherhood, it also becomes clear that her best friend, the default queen of East Side Los Angeles, Regina Mark, might not actually be a friend at all. As Leanne begins to investigate and undermine Regina, she also strikes up an unexpected friendship with the lauded writer Maxine Hunter. Feeling frustrated and invisible next to Regina's wealth and social standing, Leanne seeks security wherever she can find it, whether that's by researching whether she should vaccinate her son, in listening to the messages she thinks her father is sending from beyond the grave, or in holding her own against a petulant student in her creative writing class. Most of all, however, she looks for it within Maxine, who offers Leanne something new. With a keen eye for the trappings of privilege, class, and the performative nature of contemporary domestic life, Morris's tender and wicked debut shows us a woman who bucks against the narrative she's been fed, only to find power in herself and the truth that emerges"--